MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIADINI MELALUI METODE DRAMATISASI SPONTAN : Penelitian Tindakan kelas pada kelompok A Taman Kanak-Kanak Assamica Perkebunan Pasir Malang Kecamatan Pangalengan Kabupaten Bandung - Masitoh, - (2014)
Penelitianinidilatarbelakangiolehmasihrendahnyakemampuanberbicaraanakkelompok A di TK Assamica yang meliputikemampuananakdalammengungkapkanpendapat,menyimak,berbicaradenganlafal yang benardanberdialogdenganteman.Adapunpenelitianinisecaraumumbertujuanuntukmempelajaribagaimanapeningkatankemampuanberbicaraanakusiadini di TK AssamicaKelompok A melaluidramatisasispontan.Tujuanumumtersebutdapatdijabarkanmenjaditujuankhusussebagaiberikut : mengetahuikondisiobjektifkemampuanberbicaraanaksebelumditerapkanmetodedramatisasispontan di Taman KanakKanakAssamica,mengetahuibagaimanapenerapanmetodedramatisasispontan di Taman KanakKanakAssamicadalammeningkatkankemampuanberbicaraanakmelaluimetodedramatisasispontan di Taman KanakKanakAssamica.Metodepenelitian yang digunakanadalahPenelitianTindakanKelas di TK AssamicaKelompok A denganjumlahsubjek 7 orang perempuandan 5 orang lakilaki.Penelitiandilakukanmelaluiduasiklusdanmasing-masingsiklusterdiridariduatindakan. Berdasarkanhasilpenelitiankemampuanberbicaraanakusiadinikhususnyapadakelompok A di TK Assamicapadasetiapsiklusnyamengalamipeningkatan. Peningkatantersebutdapatterlihatpadasemakinbanyakanak yang senangberceritadanberbagipendapatdenganteman, anaksenangmengungkapkanpendapatdanmenceritakanpengalamansederhana, anakseringberdialogdenganteman. Motifasiberbicaraanak yang pelafalanhurufnyabelumjelasmenjadibaik.Rekomendasibagi guru pendidikananakusiadini , agar dalampelaksanaanpembelajarankhususnyadalammeningkatkankemampuanberbicaraanak, guru memilikiberbagaimetode yang lebihmenarikdansesuaidengancarabelajaranakusiadinisehinggamembuatanakmenyenangkandantermotivasimengikutinya. This research is motivated by the low power of speech in preschool children in group Aassamica which includes children's ability to express their opinions, listening, speaking with correct pronunciation and dialogue with friends. The general aim of this research is to study how an increase in the ability to speak early childhood in kindergarten through dramatization assamica Group A common spontan.Purpose can be translated into the following specific objectives: determine the objective conditions of the child's ability to speak before applied method of spontaneous dramatization in Kindergarten assamica, knowing how the application of the method of spontaneous dramatization in kindergarten assamica in improving children's ability to talk through spontaneous dramatization method in kindergarten Assamica.Metode study is a kindergarten classroom action research in assamica Group A with the number of subjects 7 women and 5 men .Research men carried through two cycles and each cycle consists of two actions. Based on the results of early childhood speech, especially in group A in kindergarten assamica on each cycle has increased. The improvement can be seen in a growing number of children who love to talk and share opinions with friends, happy children express their opinions and share the experience simple, children are often in dialogue with friends. Motivation speaking child who is not yet clear pronunciation of the letters to be good. Recommendations for early childhood education teachers, for the implementation of learning, especially in improving the child's ability to speak, the teacher has a more interesting variety of methods and in accordance with the early childhood learning how to make fun and motivated children to follow.